A contribution to the aphid fauna (Hemiptera: Aphididae) of Wrangel Island - Stekolshchikov, Andrey V.; Khruleva, Olga A. (Zootaxa, 2014)
Five aphid species collected on Wrangel Island (Russia) are presented. One species, Aphis polaris sp. nov., feeding on Astragalus alpinus L. and Oxytropis sp., is described, and the fundatrix morph of two others, Pterocomma groenlandicum Hille Ris Lambers, 1952 and Metopolophium sabihae Prior, 1976., is described for the first time.